2018
DOI: 10.13168/cs.2018.0040
|View full text |Cite
|
Sign up to set email alerts
|

MICROSTRUCTURE, MECHANICAL PROPERTIES AND FRICTION/WEAR BEHAVIOR OF HOT-PRESSED Si₃N₄/ BN CERAMIC COMPOSITES

Abstract: Nano-scale and micro-scale hexagonal boron nitride (hBN) powders, respectively, were added to silicon nitride (Si 3 N 4 ) matrix powder, and Si 3 N 4 /BN ceramic composites with different content of solid-lubrication hBN were produced by hot pressing. The combined effect of starting powder and hBN content on the microstructure, mechanical properties and tribological properties of Si 3 N 4 /BN ceramic composites has been studied. The results showed that the nano-sized starting powder was beneficial to the densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Research in the field of ceramic materials has shown that addition of suitable secondary phase into silicon nitride matrix can significantly influence physical, mechanical and tribological properties of created ceramic composite materials. The secondary phases can be added in form of ceramic micro and nano particles (SiC, Al 2 O 3 , ZrO 2 , TiN, TiC, hBN…), whiskers, or fibres [6,[20][21][22]. Invention of carbon nanomaterials (nanofibers, nanotubes, graphenes) caused progress in composite materials research because of utilising of their progressive properties [23,24].…”
Section: Effect Of Mechanical Properties On Wearmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in the field of ceramic materials has shown that addition of suitable secondary phase into silicon nitride matrix can significantly influence physical, mechanical and tribological properties of created ceramic composite materials. The secondary phases can be added in form of ceramic micro and nano particles (SiC, Al 2 O 3 , ZrO 2 , TiN, TiC, hBN…), whiskers, or fibres [6,[20][21][22]. Invention of carbon nanomaterials (nanofibers, nanotubes, graphenes) caused progress in composite materials research because of utilising of their progressive properties [23,24].…”
Section: Effect Of Mechanical Properties On Wearmentioning
confidence: 99%
“…The increase of the fracture toughness was caused by the deflection of crack where SiC particles were the obstacles for the propagated cracks. It is supposed that if the particles are adequately small in comparison to the critical length of the cracks, their presence in the matrix does not decrease the fracture toughness of composite [6,31]. For composite samples with addition of 20 vol.% SiC, the decrease of fracture toughness was observed, and this decrease is the consequence of the matrix morphology on the fracture toughness.…”
Section: Effect Of Mechanical Properties On Wearmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Si 3 N 4 -hBN ceramic composites, the binding capacity of hBN and ceramic matrix is poor, and excessive addition of hBN will cause the ceramic composites to lose their original high strength and high hardness. According to existing research findings [11] , the layered ceramic materials made by adding metal Mo as weak surface layer have good corrosion resistance and can achieve toughening effect of ceramic materials. Based on this, we add Mo interface layer to Si 3 N 4 ceramic composites to prepare Si 3 N 4 /Mo layered composites, and explore its physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 98%
“…Our group has been devoted to the tribological research of Si 3 N 4 ceramic composites in various fields, and the developed Si 3 N 4 -hBN ceramic composites have certain practical functions in many fields [9][10][11][12][13][14][15][16][17] . However, in Si 3 N 4 -hBN ceramic composites, the binding capacity of hBN and ceramic matrix is poor, and excessive addition of hBN will cause the ceramic composites to lose their original high strength and high hardness.…”
Section: Introductionmentioning
confidence: 99%